YOUNGER HYPERTENSIVE PATIENTS HAVE LOWER HEALTH-RELATED QUALITY OF LIFE AND DIFFERENT HYPERTENSION CORRELATES. EVIDENCE FROM BULGARIA - Emilia Naseva; Konstantin Ramshev; Nikola Ramshev; Doroteya Shtereva-Tzouni; Malina Gardeva; Vlayko Vodenicharov (Peytchinski Publishing, 2024)
The purpose of this study was to determine hypertension correlates among the patients' survey characteristics after splitting the sample into two groups based on their age and perform this assessment separately for each of the groups. Materials and methods. A cross-sectional retrospective study among 647 patients was conducted using self-administered EQ-5D 3L, as well as demographic, economic and health questions. Results. The overall self-reported arterial hypertension (AH) prevalence was 36.9%. The sample was split into two groups: 18-54 and 55+ years, with AH prevalence of 23.5% and 51%, respectively. The differences between AH and non-AH patients in each age group were explored. Younger AH patients significantly more often reported fatigue, headache, chest pain and having at least 1 acute condition for the last year than non-hypertensive ones at the same age. Diabetes, asthma/chronic bronchitis and joint pain/arthritis were also more common among younger AH patients. The overall HRQol and self-perceived health were significantly lower among young hypertensive patients, and their median severity index was higher compared to non-hypertensive adults of the same age. They more often experienced moderate pain/discomfort and moderate anxiety/depression. Despite of this, older AH patients reported similar HRQoL compared to non-AH patients. Conclusions. Different comorbidities were found amongst younger and older hypertensive patients. Most of the already known AH correlates were confirmed only among younger adults (18-54 years old). Arterial hypertension leads to significantly lower health-related quality of life, self-perceived health and higher severity index only among the younger group, mainly due to the depression and pain they experience.